2017
DOI: 10.1007/s10696-017-9288-4
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable sourcing of strategic raw materials by integrating recycled materials

Abstract: In this paper we investigate a manufacturer's sustainable sourcing strategy that includes recycled materials. To produce a short life-cycle electronic good, strategic raw materials can be bought from virgin material suppliers in advance of the season and via emergency shipments, as well as from a recycler. Hence, we take into account virgin and recycled materials from different sources simultaneously. Recycling makes it possible to integrate raw materials out of steadily increasing waste streams back into prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…[30] designed the reverse flow of the waste of plastic with a sustainable approach. Rogetzer et al [31] researched recycling materials with a sustainable approach. Two study sources provided a new way to predict the cost at the early stage for EOL products by specifying the best EOL option with the AHP method [32,33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…[30] designed the reverse flow of the waste of plastic with a sustainable approach. Rogetzer et al [31] researched recycling materials with a sustainable approach. Two study sources provided a new way to predict the cost at the early stage for EOL products by specifying the best EOL option with the AHP method [32,33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This has formed a moderate power of suppliers where they have significant roles in supplying and determining the level of raw materials inventory in the production warehouse of CGB. The coalition of suppliers to increase or fix the raw materials' prices will influence the stocks of raw materials available in the markets (Rogetzer et al, 2018). Therefore, to reduce the fluctuation of raw materials prices supplied by the suppliers, the CGB can sign contracts with its raw materials suppliers for agreed prices and terms to reduce the risks.…”
Section: Bargaining Power Of Suppliersmentioning
confidence: 99%
“…They showed that recycled materials comprise a strategic supply source leading to higher production quantities and profits. Rogetzer, Silbermayr, and Jammernegg (2018) considered a firm's sourcing strategy in a single-period setting with uncertainties in recycling quantity and price under random demand. Unlike the literature on contingent sourcing discussed earlier, this firm considered the reliable supplier (i.e.…”
Section: Recycled Materials As a Supply Sourcementioning
confidence: 99%
“…Rogetzer, Silbermayr, and Jammernegg (2019) also considered a firm's sourcing strategy in a single-period setting with random demand, uncertain yield, uncertain prices of recycled and virgin materials. However, differing from Rogetzer, Silbermayr, and Jammernegg (2018), they regard the suppliers of recycled and virgin materials as the main supplier and the backup supplier, respectively, and consider that the firm uses an options contract with the main supplier to mitigate supply risk.…”
Section: Recycled Materials As a Supply Sourcementioning
confidence: 99%